EFFECTIVENESS OF RELAPSE PREVENTION THERAPY ON BIO-PSYCHO–SOCIAL PARAMETERS AMONG INDIVIDUAL AND DYADIC GROUP ALCOHOL DEPENDENTS - PROF. MRS.VANITHA INNOCENT RANI, M.Sc (N)., RN,RM.,(Ph.D.,), (International Journal of Pharma and Bio Sciences, 2016)
The effectiveness of RPT on bio-psycho –social parameters among 24 alcohol dependents were done in selected de-addiction centers at Thanjavur district. 12 samples were in experiment and 12 were in control group samples were selected by using the cluster sampling Technique. True experimental pre test – post test control group design were used. Data were collected through interview method by using 3 standardized Questionnaires, 1 semi –structured questionnaire and laboratory test method was used to assess the bio-psycho-social parameters. The obtained paired ‘T’ test score had significant effect on ‘P’ Value < 0.05 in biological parameters (Audit) – psycho-social parameters in experimental group. It indicates the given RPT was effective in both IAD & DAD . There was a highly positive significant correlation in experimental group. The obtained unpaired ‘t’ test score for comparison between experimental and control groups showed a significant difference in bio(Audit) Psycho-Social parameters of the experimental group alone .The comparison between IAD & DAD group had significant difference in Bio (Audit) psycho social parameters of the experimental groups. Hence the study result revealed that RPT was effective for the experimental groups. And RPT with Care givers support was more effective in DAD experimental group. So RPT with care givers support was more effective on bio-psycho-social parameters of alcohol dependents.